Optimalisasi Penggunaan Invoice dan Nota sebagai Alat Kontrol dan Dokumentasi Transaksi: (Studi pada House Tapis Citra Bandar Lampung) - Amir, Aprilianto; Suryani, Suryani; Sundari, Susanti; Nur, Cahya (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
Invoices and notes are important tools in a company's financial management process. The sustainability of a business requires high accuracy and integrity of transaction data. House Tapis Citra as a business engaged in the arts and culture of Lampung, especially clothing and accessories, needs to adopt the use of invoices and notes that refer to the right standards. This study focuses on optimizing the use of invoices and notes as important supporting tools in achieving the effectiveness and efficiency of financial transactions at HTC. This study aims to design a more effective and efficient system in managing transaction documents by analyzing various factors that affect data accuracy, including document formats, recording procedures, and information systems used. Keywords: invoices, notes, optimization, transaction